The Use of Social Media by Small-Medium Sized Enterprises. - Huson, Oliver (2011)
Purpose – The purpose of this paper is to report on the suitability of Social Media and its purpose in small-medium sized enterprises (SMEs). The objective is to develop an understanding of an owner-managers use of Social Media; the possible roles these tools can perform in marketing and business practices and whether or not the tools needs to tailored, changed or adapted to be used in the SME context.